Artificial Intelligence and Its Role in Educational Development: Toward More Personalized and Efficient Education - اعبودي, ابتهال أسمر (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study aims to explore the relationship between artificial intelligence (AI) and educational development by examining the fundamental concepts, practical applications, and challenges associated with integrating this advanced technology into educational contexts. The research focuses on identifying the theoretical frameworks of AI and its application areas in enhancing the quality of education, such as adaptive learning, intelligent assessment, digital assistants, and educational data analytics, with a particular focus on the Arab world's experience in this domain. The study highlights how the AI revolution has contributed to transforming the educational environment by supporting researchers, personalizing learning experiences, and providing flexible and inclusive educational opportunities. It further discusses the positive impacts of AI in education, including improved interaction, time efficiency, and enhanced learning outcomes. Conversely, it addresses potential negative consequences of unregulated AI use, such as algorithmic bias, reduced human interaction, and the widening digital divide. Moreover, the research sheds light on future challenges facing the integration of AI in educational systems, including scientific, ethical, pedagogical, and social challenges. It offers recommendations aimed at promoting the safe, effective, and equitable use of AI within a sustainable educational environment. The study concludes that the successful implementation of AI in education requires an integrated approach encompassing robust digital infrastructure, continuous professional development, appropriate legislation, and a clear educational vision.